EFFECTS OF TRANSPORT ON WELFARE AND QUALITY OF BEEF CATTLE - DINIZ, P. P.; SILVA, B. L.; PEREIRA, V. V.; GRANDE, P. A. (Revista Brasileira de Engenharia de Biossistemas, 2011)
The main reason for this review was to do a study to show how the inappropriate animals handling and the road transportation on the farm are important factors of the economic losses caused by the carcasses injuries, as a result, the inspection system rejection during the slaughtering. The road transportation is the most commom way of taking animals to the slaughtering. The inappropriate road transportation can cause the animals death, contusions, weight loss and stress. The increase of stress during the transportationis caused by the adverse conditions like scarcity of food and water, high moisture, high air speed and load density. The main aspect to be considerate during bovines transportation is the spot took for animal, in other words, the load density, that can be classified as high (600 Kg/m²), medium (400 Kg/m²) and low (200 Kg/m²). Thus, the purpose of this bibliography review is to do a survey of the main factors during the bovines transportation that are related to the quality losses and carcasses injuries and carcasses compensation.